A study on comparison of potential anthelmintic activity between papaya seeds and papaya latex on hymenolepis diminuta infection in rats - Arney Sapaat (2012)
The purpose of this study is to compare the potential anthelmintic activity between papaya seeds and papaya latex on Hymenolepis diminuta in rats.The objectives of this study are to determine the effectiveness of papaya seeds and papaya latex on helminths especially Hymenolepis diminuta in rats, to determine the effective dose level on helminths in rats, and to compare the anthelmintic activity between the papaya seeds and papaya latex. To conduct this study, 36 male rats from strain Sprague-Dawley were used. Two dose levels were used for papaya seeds treatment which are 0.6 g kg-1 and 1.2 g kg-1. For papaya latex treatment, the doses are 4 g kg-1 and 8 g kg-1. The geometric mean (GEM) were used to calculate mean for eggs per gram (EPG) before and after the treatment to be included in the reduction percentage calculation. After 21 days post treatment, necropsy were done to get the worm count and the GEM of it were used to calculate the efficacy percentage for both papaya seeds and papaya latex treatment. Results from this study shows that the reduction percentage in EPG for papaya seeds treatment for both doses level are very high which is 96.8% for 0.6g kg-1 dose level and 96.2% for 1.2 g kg-1 dose level. Whereas the eficacy percentage based on the worm counts for both doses level also very high that is 90.8% for 0.6 g kg-1 dose level and 93.9% for 1.2 g kg-1. Differently from the papaya latex treatment that give only an acceptable results for the reduction percentage in EPG that is 72.8% with the efficacy percentage of 53.9% for 4 g kg-1 dose level and reduction percentage of 86.2% with eficacy percentage of 73.9% for 8 g kg-1 dose level.